The Impact of Digital Access and Literacy on Women's E-Commerce Adoption in the Philippines - Policarpio, Rona Jane; Magpantay, Ederliza (Faculty of Science and Technology University of Pramita Indonesia, 2024)
The primary objective of this study was to investigate the influence of Filipino women's existing digital access and literacy levels on their adoption of e-commerce. The researcher utilized the Multivariate Linear Regression Model via Ordinary Least Squares (OLS) Regression in exploring and quantifying the relationship and influence of the regressors and regressand. The OLS estimates suggest that higher data privacy awareness correlates with increased e-commerce adoption of women for purchasing goods and services online. On the other hand, improved digital skills are linked to increasing women's e-commerce adoption in terms of selling goods and services online. The two regression models have different significant variables, implying that consumers and sellers prioritize different factors when deciding to adopt e-commerce.